Strengthening the Interaction of the Virology Community with the International Committee on Taxonomy of Viruses (ICTV) by Linking Virus Names and Their Abbreviations to Virus Species. (28th January 2019) - Calisher, Charles H; Briese, Thomas; Brister, J Rodney; Charrel, Rémi N; Dürrwald, Ralf; Ebihara, Hideki; Fulhorst, Charles F; Gāo, George Fú; Groschup, Martin H; Haddow, Andrew D; Hyndman, Timothy H; Junglen, Sandra; et al.
Abstract: The International Committee on Taxonomy of Viruses (ICTV) is tasked with classifying viruses into taxa (phyla to species) and devising taxon names. Virus names and virus name abbreviations are currently not within the ICTV's official remit and are not regulated by an official entity. Many scientists, medical/veterinary professionals, and regulatory agencies do not address evolutionary questions nor are they concerned with the hierarchical organization of the viral world, and therefore, have limited use for ICTV-devised taxa. Instead, these professionals look to the ICTV as an expert point source that provides the most current taxonomic affiliations of viruses of interests to facilitate document writing. These needs are currently unmet as an ICTV-supported, easily searchable database that includes all published virus names and abbreviations linked to their taxa is not available. In addition, in stark contrast to other biological taxonomic frameworks, virus taxonomy currently permits individual species to have several members. Consequently, confusion emerges among those who are not aware of the difference between taxa and viruses, and because certain well-known viruses cannot be located in ICTV publications or be linked to their species. In addition, the number of duplicate names and abbreviations has increased dramatically in the literature. To solve this conundrum, the ICTV could mandate listing all viruses of established species and all reported unclassified viruses in forthcoming online ICTV Reports and create a searchable webpage using this information. The International Union of Microbiology Societies could also consider changing the mandate of the ICTV to include the nomenclature of all viruses in addition to taxon considerations. With such a mandate expansion, official virus names and virus name abbreviations could be catalogued and virus nomenclature could be standardized. As a result, the ICTV would become an even more useful resource for all stakeholders in virology.